The peculiarity of usage of compound words “verb+noun” in Chinese language (Journal of Oriental Studies, 2016)
To the form of compound words “verb+noun” can be added other elements and it will look as a collocation, but it has meaning of just one word. Such words in Chinese language considered as a special language phenomenon and researched with title离合词.. Here离(dined),  合(join),  词(word). And that means it used as divided and as a cornpounded.This article reveals scientific analyses of errors made by students studying chinese language while implementation of complex verbs in the form “verb + noun” and tells us about correct ways of their usage.
Keywords: collocation; word; compound words; compound verbs